2014
DOI: 10.1590/0103-6440201300096
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical Properties of a Methacrylate-Based Dental Adhesive Incorporated with Epigallocatechin-3-gallate

Abstract: This study aimed to evaluate the influence of epigallocatechin-3-gallate (EGCG) incorporation on the physicochemical properties of a methacrylate-based dental adhesive. EGCG was added to Adper Easy One (3M-ESPE) except in control group, to obtain concentrations of 0.01% w/w and 0.1% w/w of EGCG-doped adhesives. For water sorption (WS) and solubility (SL) surveys, resin discs were assayed following ISO recommendations (n=10). The degree of conversion (DC) was analyzed by FTIR whereas flexural strength (FS) was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 23 publications
1
15
1
Order By: Relevance
“…The results presented in this study are consistent with Neri, et al 30 (2014), who observed that adhesives with EGCG concentrations at 0.01 wt% and 0.1 wt% did not differ in flexural strength or percentage of water sorption of the adhesives, which showed no differences in their physical or chemical properties at these different concentrations. EGCG is known to promote collagen cross-linking through hydrogen bonding, thus improving collagen properties such as modulus of elasticity 9 .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The results presented in this study are consistent with Neri, et al 30 (2014), who observed that adhesives with EGCG concentrations at 0.01 wt% and 0.1 wt% did not differ in flexural strength or percentage of water sorption of the adhesives, which showed no differences in their physical or chemical properties at these different concentrations. EGCG is known to promote collagen cross-linking through hydrogen bonding, thus improving collagen properties such as modulus of elasticity 9 .…”
Section: Discussionsupporting
confidence: 92%
“…The physical and mechanical properties of adhesives strongly depend upon the degree of conversion 30 . Therefore, higher values of mechanical and physical properties were expected for EGCG-doped adhesives due to the possible hydrogen bond established between EGCG and Bis-GMA.…”
Section: Discussionmentioning
confidence: 99%
“…At concentrations of 0.5% and 1% (w/v), EGCG incorporated in an adhesive resin could increase the bond strength values and the longevity of adhesive-dentin bond for 6-12 months [44,45]. In contrast to the previous investigation, the addition of 0.01 and 0.1% (w/v) of EGCG to adhesive-resin compounds did not affect the resin-dentin bond, but could reduce the solubility of the adhesive-resin in water [42]. Yu et al [46] showed that EGCG, in addition to its antibacterial activity, increases the bond strength of root canal sealer to dentin.…”
Section: Dentin Modifier Dentin Pretreatment Collagen Cross-linkingcontrasting
confidence: 62%
“…In addition to those properties, EGCG was incorporated in dental adhesive-resins for its inhibitory effects of matrix-metalloproteinases (MMPs) and cysteine cathepsins. Indeed, those proteins are major players in the degradation and perturbation of the resin-dentin interface [42,43].…”
Section: Dentin Modifier Dentin Pretreatment Collagen Cross-linkingmentioning
confidence: 99%
“…Du et al 37 reported that the incorporation of epigallocatechin-3-gallate (EGCG), which is a GA derivate into a dental adhesive, had favorable therapeutic effects such as increased antibacterial activity as well as improved microtensile bond strength. In another study by Neri et al 38 the addition of EGCG into a self-etch bonding agent showed no adverse effects on the degree of conversion and flexure strength values. Hu et al 39 investigated the physical properties of glass ionomer cements after the addition of EGCG and revealed improved flexural strength and surface hardness values in comparison with those of the control groups.…”
Section: Discussionmentioning
confidence: 92%